2009
DOI: 10.1108/17471110910964478
|View full text |Cite
|
Sign up to set email alerts
|

CSR activities in award‐winning Thai companies

Abstract: PurposeThis case‐study research aims to examine best CSR practices in four Thai companies that were given CSR awards. The purpose is to report on best practices in CSR in Thailand.Design/methodology/approachFour Thai companies that received the best CSR awards from the Stock Exchange of Thailand (SET) in 2006 were selected. The data were collected through a questionnaire, interviews, and company documents and web sites.FindingsCSR activities in the top Thai companies were based on moral or altruistic motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
0
42
0
1
Order By: Relevance
“…Ironically, it was found that only a few managers agreed with the role of corporate houses in poverty reduction. Virakul, Koonmee, and McLean () conducted a study on four top Thai companies and found that their CSR framework mainly addressed five categories: education, arts and culture, sports, environment and public welfare. Leonidas et al () found that in Greece CSR programs were mostly oriented towards society, the environment and employees.…”
Section: Resultsmentioning
confidence: 99%
“…Ironically, it was found that only a few managers agreed with the role of corporate houses in poverty reduction. Virakul, Koonmee, and McLean () conducted a study on four top Thai companies and found that their CSR framework mainly addressed five categories: education, arts and culture, sports, environment and public welfare. Leonidas et al () found that in Greece CSR programs were mostly oriented towards society, the environment and employees.…”
Section: Resultsmentioning
confidence: 99%
“…The data collected have shown that CSR activity taking place in these particular cases has been project-managed. This applies across strategic programmes for youth engagement and more basic and (Virakul, Koonmee, & McLean, 2009, p. 1991 "This is what our CEO believes, and then this is what the organization believes", therefore it's more DNA like, business like." "… the way leadership decides it, that's the way the ship is going to sail."…”
Section: Discussionmentioning
confidence: 86%
“…Corporate Social Responsibility (CSR) Virakul, Koonmee, and McLean (2009) define CSR as ''the set of philosophy, policy, motivations, commitment, and activities of business companies that consider balancing requirements for financial profits with the benefits of all involved stakeholders.'' More recently, Aguinis (2011, p. 179) captured several key elements of CSR and defined it as ''context-specific organizational actions and policies that take into account stakeholders' expectations and the triple bottom line of economic, social, and environmental performance'' (855).…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%
“…Large organizations may appear more prepared to apply the proposed model. However, leadership, qualified managers, and adequate resources are more critical to the success of HR=CSR activities than the size of an organization (Virakul et al 2009). Given that the factors exist, small, medium, or large organizations would have equal opportunity of success in achieving the proposed performance on their own terms.…”
Section: The Role Of Human Resource Management (Hrm) and Human Resourmentioning
confidence: 99%
See 1 more Smart Citation